Subcritical water extraction as an environmentally-friendly technique to recover bioactive compounds from traditional Serbian medicinal plants - Nastić, Nataša (2020)
Subcritical water extraction (SWE) has become a popular green extraction technique for the isolation of different classes of compounds from natural matrices. Low price, safety and green character of water, good yields of target compounds and reduced energy consumption, make this technique favorable for potential industrial applications. The purpose of this study was to evaluate antioxidant, antimicrobial and cytotoxic activity of four medicinal plants traditionally used in folk medicine of Serbia. Black mulberry (Morus nigra L.), wall germander (Teucrium chamaedrys L.), wild geranium (Geranium macrorrhizum L.) and comfrey (Symphytum officinale L.) were extracted by subcritical water at different temperatures. Antioxidant activity of the extracts was defined by conventional spectrophotometric methods, such as the total phenolic content (TPC), DPPH-radical scavenging activity (DPPH-RSA), ferric reducing antioxidant power (FRAP) and total antioxidant capacity (TAC) assessed by a DNA-based sensor. Additionally, the main phenolic compounds contributing to the antioxidant activity of the produced extracts were also identified and quantified by high performance liquid chromatography with diode array detection (HPLC-DAD). Antimicrobial properties of extracts were evaluated against eight microbial strains. Furthermore, the cytotoxic activity was observed for two human cancer cell lines and a cell line derived from murine fibroblast.